Coaching Methods for Forming Religious Character and Responsibility in Community Students (Case Study at the Special Development Institute for Class I Children in Blitar City) - Hajizah, Aditya Nur Widi; Purwito, Lasi; Purnamasari, Ica (Proceedings Series of Educational Studies, 2024)
This research was used to identify coaching methods to shape the character of children in the Special Development Institute for Class I Children in Blitar City. This research was conducted using qualitative research methods with data collection process through observation, interviews and documentation techniques. LPKA Class I Blitar City's efforts to make andikpas have the awareness to worship. Apart from worship, the cultivation of religious character values can also be seen when correctional students are happy to help friends who are experiencing difficulties, comforting friends who feel sad. Apart from that, Andikpas also increasingly understands its responsibilities. The coaching method used by LPKA Class I Blitar City to improve the religious character of correctional students is by using the method of example, habituation and advice. Meanwhile, the coaching method used by the Class I Special Development Institute for Class I Children in Blitar City to improve the responsible character of correctional students is by using the exemplary method and also the habituation method.